Intestinal Ultrasound's New Target: Idiopathic Mesenteric Vein Sclerosing Enteritis - Qianjiang Luo; Xiaoshan Huang; Zhong Zheng; Luhong Zhu; Mei Luo; Wenxing Zhang; Qinglian Zhong; Jian Huang; Yuhang Zhou; Jin Li; Wanjie Zhu (JGH Open)
ABSTRACT Introduction As a rare clinical entity within the non‐thrombotic ischemic colitis spectrum, idiopathic mesenteric phlebosclerotic colitis (IMPC) has been increasingly recognized to exhibit a pathogenic correlation with extended herbal medicine consumption. Case Presentation A 48‐year‐old female complained of abdominal pain for over 3 years was diagnosed IMPC and concurrent Entamoeba coli infection. The patient underwent non‐targeted pharmacotherapy, which yielded poor results. In this case, we introduced a non‐invasive diagnostic tool, gastrointestinal ultrasound (GIUS), to assist in the diagnosis. Additionally, we observed this patient developed opportunistic infections of the gastrointestinal tract, a phenomenon that appears to be associated with compromised immune function and reduced microbial defense capabilities. Conclusion Gastrointestinal ultrasound was introduced to assist in diagnosis of IMPC in this case. Currently, treatment options for severe IMPC are limited, highlighting the need for further research into its mechanisms and therapeutic approaches.